Formation of sprint running technique by directed development of separate muscle groups' strength in young athletes - Arakelyan, E. E.; Zbarsky, V. A.; Shevchenkom, T. N.; Seluyanov, N. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
he purpose of this study was to reveal the influence of the power training, using the system of the alleviated lead (SAL) on the sprint technique's parameters. 48 runners aged for 11 to 12, distributed in 4 groups acted as subjects of the pedagogical experiment. The training machine "SAL" had been used in three experimental groups two times a week. The results of the 6 week's experiment had shown that the usage of SAL in sprints training allows to increase the rate of running, when realizing the draught forward, and to increase the push power, when realizing the draught back. If each exercise performs till the local fatigue (8-20 c) repeating 3-5 times twice a week, it leads to the significant growth of the powers opportunities in the muscles, bending and straightening lower extremities in the hip join, and to the changes in the stride's length and running rate, if compared with the control group's sprinters.